Bimbingan Teknis Penggunaan Aplikasi Pencatatan Informasi Keuangan pada Kelompok Pengrajin Tenun - Ernawati Malik; Dewi Mahmuda; Muhammad Rahman Al Akbar; Wa Ode Elfianti; Endang Tri Pratiwi (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
The purpose of this PkM activity is to provide technical guidance to groups of weaving craftsmen regarding the financial management of business units using the SIAPIK application (Financial Information Recording Application Information System). This technical guidance was carried out on a group of weaving craftsmen in the Wabula Traditional Village, Wabula District, Buton Regency with the formulation of the activity theme obtained through a preliminary survey of the weaving craftsman group which was delivered during the visit and the initial discussion between the PkM team and the weaving craftsman group. Based on the results of the discussion, the problems faced by the weaving craftsmen group today are (1) business activities that take place continuously, but there is no profit accounting; (2) limited knowledge of the group of weaving craftsmen regarding the financial management of technology-based business units. This technical guidance is carried out through a Participatory Training approach with a series of preliminary, implementation and evaluation stages. The results of the evaluation of PkM activities showed that the initial understanding of the weaving craftsman group towards financial management was in the range of 40% before the technical guidance was implemented, then increased to 80% after the technical guidance was implemented.